AJARAN TASAWWUF DALAM PITUTUR SHEH BARI Studi Atas Buku The Admonation Of Sheh Bari - Abd. Djalal (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2014)
This paper describes a study of Indonesian Islamic studies performed famous orientalist from University of Leiden, Netherlands, GWJ Drewes, The Admonation of Sheh Bari. The Admonation of Sheh Bari edited and reviewed, Pitutur Sheh Bari, which contains the teachings fana has been taught by the Muslim Sufis such as al-Ghazali and al-Qushairi. But in the PituturÂ  Sheh Bari stained with Javanese mysticism as Manunggaling Kawulo Gusti. Thus this paper was going to show one more data and evidence that acculturation process between Javanese traditions and the teaching of Islam. This is one of the characteristics of Islam in Indonesia.